2021
DOI: 10.31219/osf.io/u7ewz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protocol violations in López-Medina et al.: 38 switched ivermectin (IVM) and placebo doses, failure of blinding, widespread IVM sales OTC in Cali, and nearly identical AEs for the IVM and control groups

Abstract: This brief communication describes protocol violations in López-Medina et al., Effect of Ivermectin on Time to Resolution of Symptoms Among Adults With Mild COVID-19: A Randomized Clinical Trial (JAMA, 2021). This study switched ivermectin (IVM) and placebo doses for 38 patients; failed to maintain blinding between IVM and placebo doses; had distinctive IVM-associated adverse effects among the controls, matching those for the IVM group, indicating over-the-counter IVM use; and had blatant conflicts of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Despite the study lead author's cooperation in producing detailed deidentified patient data in response to other queries, he has refused repeated queries to specify the composition of this new placebo solution. 23 Until this question is answered and other procedural violations are clarified, this study's findings cannot be considered reliable.…”
Section: Six Recently Published Studies In Mainstream Scientific Journalsmentioning
confidence: 85%
See 2 more Smart Citations
“…Despite the study lead author's cooperation in producing detailed deidentified patient data in response to other queries, he has refused repeated queries to specify the composition of this new placebo solution. 23 Until this question is answered and other procedural violations are clarified, this study's findings cannot be considered reliable.…”
Section: Six Recently Published Studies In Mainstream Scientific Journalsmentioning
confidence: 85%
“…10 However, this study was severely compromised by protocol violations including mistaken substitution of IVM for placebo in 38 of the first 75 patients, discovered a month after the fact by the study's lead pharmacist. 23 Extensive use of over the counter IVM, sales of which surged in Cali during the study period, were indicated in the placebo group. Blinding was violated by the use of glucose solution for the first one-third of the patients in the control group, whereas IVM has a bitter taste.…”
Section: Six Recently Published Studies In Mainstream Scientific Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Popp 1 thus exhibits smaller and poorer-quality data for in-patient mortality than already available more than a year earlier. Even including the outpatient analysis in Popp 1 (a single death in 422 patients, most from the widely-criticised 48,23 Lopez-Medina study 49 ) the Popp 1 evidence is still far smaller than the WHO guideline 46 from 1419 participants, which though deprecating ivermectin nevertheless quotes a mortality Odds Ratio of 0.19 with narrow Confidence Intervals. Bryant 3 covers 2038 patients (even after the removal of a disputed study 47 ).…”
Section: The Mortality Outcomementioning
confidence: 96%
“…52 One of the few outliers among these 20 RCTs, which reported statistically indistinguishable outcomes for its IVM and control groups, 53 had similar serious errors, with 38 doses of IVM mistakenly substituted for placebo and blinding violated with a glucose placebo. 54 Among the most recent and comprehensive of the eight meta-analyses noted above reported a pooled total of 31 deaths among 1,101 subjects in IVM treatment groups and 91 deaths among 1,064 controls from 11 RCTs, amounting to a 67% reduction in mortality, with a statistical significance for overall effect of p=0.005. 46 Two animal studies of IVM treatment at low human-equivalent doses, one for SARS-CoV-2 in golden hamsters 55 and another for a related betacoronavirus (MHV-A59) in mice, 56 found major, highly statistically significant treatment benefits, consistent with those found in the RCTs noted above.…”
Section: Introductionmentioning
confidence: 97%